Climate Change in the Himalayas : Current State of Knowledge - Gautam, Mahesh R.; Timilsina, Govinda R.; Acharya, Kumud (World Bank, Washington, DC, 2013)
This paper reviews the literature on the potential biophysical and economic impacts of climate change in the Himalayas. Existing observations indicate that the temperature is rising at a higher rate in Nepal and Chinese regions of the Himalayas compared with rest of the Himalayas. A declining trend of monsoon in the western Indian Himalayas and an increasing trend in the eastern Indian Himalayas have been observed, whereas increasing precipitation and stream flow in many parts of Tibetan Plateau are noted. Glaciers in both the eastern and western Himalayas are mostly retreating, but the majority of the glaciers in Karakorum are either stable or advancing slowly. Expansion of glacier lakes is reported, with the highest rate in Nepal and Bhutan. Most literature predicts increases in temperature and monsoon precipitations and decreases in winter precipitations in the future thereby leading to monsoon flooding and increased sediments in stream flow. Available hydrological simulations indicate reduced rainfall and shrinkage of glacier thereby leading to shortage of water supply for power generation and irrigation in winter particularly in highly glaciated basins. Projected economic impacts of glacial lake outburst floods can be substantial on the developed river basin with infrastructures and population centers. However, there is a clear gap in knowledge of economic impacts of climate change in the Himalayas.